New trends in diagnostic and therapeutic approach to liver and pancreas diseases - Klincewicz, Beata; Kobelska-Dubiel, Natalia; Cichy, Wojciech (Przewodnik Lekarza/Guide for GPs, 2011)
In the presented paper, based on the recent data, the authors discussed the selected pancreas and liver diseases. The diagnostic and therapeutic methods were analyzed. The epidemiology and some pathophysiologic issues were mentioned.